IMMU-02. LOCOREGIONAL HER2CAR T CELLS FOR PEDIATRIC CENTRAL NERVOUS SYSTEM TUMORS: PRECLINICAL EFFICACY TO TOLERABILITY IN FIRST PATIENT. (23rd April 2019) - Vitanza, Nicholas; Johnson, Adam; Beebe, Adam; Gust, Juliane; Hauptman, Jason; Hoeppner, Corrine; Wilson, Ashley; Perez, Francisco; Pinto, Navin; Orenta, Rimas; Finn, Laura; Gardner, Rebecca; et al.
Abstract: Chimeric antigen receptor (CAR) T cell therapy provides a broadly applicable, targeted, yet pathway-independent, intervention for pediatric central nervous system (CNS) tumors. We have optimized the efficacy and specificity of a HER2-targeted CAR with an extracellular target-specific scFv domain derived from trastuzumab (a HER2 targeting antibody), a co-expressed truncated EGFR (EGFRt) to evaluate transduction efficacy and as a potential suicide mechanism with cetuximab treatment, and a medium-length spacer coupled to an intracellular 4-1BBζ domain. In vitro studies revealed antigen specific cytotoxicity and cytokine release against HER2-positive CNS tumors; and the HER2CAR significantly improved survival (p=0.003) in vivo at 90 days in a xenograft CNS model relative to Mock-treated controls. BrainChild-01 is a first-in-human trial evaluating locoregional infusion of HER2CAR T cells for children and young adults with HER2-positive progressive or recurrent CNS tumors. Autologous T cells are apheresed, engineered to express the second-generation HER2CAR, and expanded ex vivo . They are delivered via indwelling CNS catheter into either the tumor cavity (Arm A) or ventricular system (Arm B) using an intra-patient dose-escalation regimen with weekly dosing for 3 of every 4 weeks per course. The study period is two courses though subjects may receive up to six. Subject 001, a 19-year-old female with a parietal lobe hypermutated HER2-positive anaplastic astrocytoma (WHO grade III), enrolled on Arm A following third progression, underwent apheresis and successful production of 1.9 x 10 9 HER2CAR T cells. She tolerated the study-prescribed six CAR T cell doses over two courses at doses of 1 x 10 7 to 2.5 x 10 7 without dose limiting toxicity. Acute local inflammation and CRP elevation followed each dose. MRI brain/spine obtained after Course 2 revealed increased enhancement and T2/FLAIR hyperintensity surrounding the tumor cavity with mildly increased mass effect, indeterminate for treatment-related inflammatory changes/pseudoprogression versus tumor progression. Enrollment is ongoing.